ANALISIS THE EFFECT OF STOCK BUYBACKS ON STOCK PRICES IN COMPANIES LISTED IN INDONESIA STOCK EXCHANGE DURING THE COVID-19 PANDEMIC PERIOD IN 2020 - Erwin Dyah Astawinetu; I Istiono; Erma Yuliaty (Universitas 17 Agustus 1945 Surabaya, 2022)
Stock repurchase is a corporate action carried out to withdraw part of the outstanding stocks in the market. There are several purposes of this action, including to increase the market price of the company's stocks. This research was to analyze the effect of stock buybacks carried out by corporations on the stock prices of companies listed on the IDX during the Covid-19 pandemic period 2020. There are 21 companies selected to be the object of this study. The collected stock price data was tested for normality and found that it was not normally distributed, so the statistical tools used were non-parametric statistics. The mean difference test is used to test the effect of the corporate action on the stock price. The results of the mean difference test show that the stock repurchase action was able to increase the stock price, although it has not matched the stock prices before the implementation of this corporate action.